2022
DOI: 10.47127/ijtmr.v7i1.148
|View full text |Cite
|
Sign up to set email alerts
|

Embracing mobile financial inclusion in the wake of Covid-19 pandemic: The mediating role of cognitive and affective-based trust embeddedness

Abstract: The aim of the study is to examine the role of social capital in the formation of mobile financialservice users’ adoptive behaviours toward service providers in the context of the financialtechnological regime of Ghana. The study used a total of 417 sample data from a self-administeredquestionnaire to achieve its objectives. Structural equation modeling was employed to analyze thedirect effects of social capital and the mediation role of cognitive-based trust and affective-based truston mobile financial servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Goel and Madan [84], Koomson and Ibrahim [85], and Adegbite and Machethe [86] suggested and proved a positive effect of financial inclusion on the sustainability of business performance in agriculture. Ampaw et al [87], Bongomin and Ntayi [88], and David et al [89] also found that financial inclusion can improve trust in extension and financial services. However, the current study is one of the first to test the impact of financial inclusion directly on sustainable farm performance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Goel and Madan [84], Koomson and Ibrahim [85], and Adegbite and Machethe [86] suggested and proved a positive effect of financial inclusion on the sustainability of business performance in agriculture. Ampaw et al [87], Bongomin and Ntayi [88], and David et al [89] also found that financial inclusion can improve trust in extension and financial services. However, the current study is one of the first to test the impact of financial inclusion directly on sustainable farm performance.…”
Section: Discussionmentioning
confidence: 99%